Spatial heterogeneity, generational change and childhood socioeconomic status : microeconometric solutions to South African labour market questions - Von Fintel, Dieter (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.